Multifunctional roles of intercropping in the management of insect pests affecting pulse crops: a comprehensive bibliometric analysis - Rachid Lamzira; Karim El Fakhouri; Rachid Boulamtat; Seid Ahmed Kemal; Ali Oubayoucef; Chaimae Ramdani; Issam Meftah Kadmiri; Mustapha El Bouhssini (Frontiers in Sustainable Food Systems)
Pulse crops such as faba beans, chickpea and lentils are an important contributor to the necessary food thanks to their richness of proteins and low-fat content, in addition to the presence of fibers and bioactive components. However, like all crops, pulse crops face many biotic and abiotic challenges that lead to a reduction in productivity and quality. Managing key biotic stresses, such as insect pests and diseases in pulse crops, primarily involves a combination of multiple strategies including cultural practices, biological control, host plant resistance, and synthetic pesticides. One of the promising cultural control approaches to address insect pest challenges is adopting intercropping as a sustainable agricultural practice. When implemented effectively, intercropping can significantly mitigate the pressure of insect pests attacking pulse crops. In addition to intercropping, semiochemicals such as pheromones and kairomones have started as a component of biorational pest management in modern agriculture. This review provides a comprehensive guide on the multifunctional roles of intercropping in the management of insect pests in pulse crops, with a focus on the role of volatile organic compounds associated with in the intercropping system.